Tradeguide: geoposicionamento em dispositivos móveis - Ebara, Rafael Mitsuo Bueno (2014)
This study was written based on the development of commercial establishments geopositioning application (location premises using geographic coordinates), TradeGuide. The application, taking as input the geographical coordinates of the user, offers a list of categorized commercial establishments, previously registered in this system, and from this list gives an access route to the selected establishment, considering the user’s initial position. It’s indicated mainly to new people in the city in need for products and services but do not know how to find it, and also as a form of establishments disclosure. This system was built in a platform Client/Server and developed in PHP programing language and partially developed for mobile devices provided by the Android operational system from version 4.0.